Active bilayer films of thermoplastic starch and polycaprolactone obtained by compression molding. (20th August 2015) - Ortega-Toro, Rodrigo; Morey, Iris; Talens, Pau; Chiralt, Amparo
Highlights: S95-PCL films formed bilayers with good adhesion and good mechanical performance. All bilayers showed excellent barrier properties to water vapour and oxygen. Addition of potassium sorbate at the interface enhanced mechanical properties. Bilayers could have active properties associated to bioactives compounds at interface. Abstract: Bilayer films consisting of one layer of PCL with either one of thermoplastic starch (S) or one of thermoplastic starch with 5% PCL (S95) were obtained by compression molding. Before compression, aqueous solutions of ascorbic acid or potassium sorbate were sprayed onto the S or S95 layers in order to plasticize them and favor layer adhesion. S95 films formed bilayers with PCL with very good adhesion and good mechanical performance, especially when potassium sorbate was added at the interface. All bilayers enhanced their barrier properties to water vapour (up to 96% compared to net starch films) and oxygen (up to 99% compared to PCL pure). Bilayers consisting of PCL and starch containing 5% PCL, with potassium sorbate at the interface, showed the best mechanical and barrier properties and interfacial adhesion while having active properties, associated with the antimicrobial action of potassium sorbate.